2019
DOI: 10.48550/arxiv.1907.05595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Jointly Adversarial Network to Wavelength Compensation and Dehazing of Underwater Images

Abstract: Severe color casts, low contrast and blurriness of underwater images caused by light absorption and scattering result in a difficult task for exploring underwater environments. Different from most of previous underwater image enhancement methods that compute light attenuation along object-camera path through hazy image formation model, we propose a novel jointly wavelength compensation and dehazing network (JWCDN) that takes into account the wavelength attenuation along surfaceobject path and the scattering al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 45 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…By comparing the 1st, 2nd and 3rd rows of Fig. 4, it can be clearly observed that the synthesized images based on [25] and [26] cannot simulate the characteristics of real underwater images well, especially in color casts. In our opinion, this is mainly caused by incorrect ambient light settings.…”
Section: A Limitations Of Existing Underwater Synthesis Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…By comparing the 1st, 2nd and 3rd rows of Fig. 4, it can be clearly observed that the synthesized images based on [25] and [26] cannot simulate the characteristics of real underwater images well, especially in color casts. In our opinion, this is mainly caused by incorrect ambient light settings.…”
Section: A Limitations Of Existing Underwater Synthesis Modelsmentioning
confidence: 99%
“…Underwater image synthesis is usually solved from two different perspectives: based on Generative Adversarial Networks (GAN) [23], [24] and physical models [25], [26]. Li et al [23] propose a deep model, named WaterGAN, to generate underwater-like images from in-air images and depth maps in an unsupervised manner.…”
Section: A Underwater Image Synthetic Datasetsmentioning
confidence: 99%
See 3 more Smart Citations